2019
DOI: 10.1136/bmjopen-2018-026872
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to care for women with low-grade endometrial cancer and morbid obesity: a qualitative study

Abstract: ObjectiveObesity is a major risk factor for low-grade endometrial cancer. The surgical management of patients with obesity is challenging, and they may face unique barriers to accessing care. We completed a qualitative study to understand the experiences of low-grade endometrial cancer patients with morbid obesity, from symptom onset to diagnosis to surgery.DesignSemi-structured interviews were performed with endometrial cancer patients with morbid obesity (body mass index (BMI)>40 kg/m2) referred for prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(70 citation statements)
references
References 35 publications
(45 reference statements)
2
67
0
Order By: Relevance
“…In our study, we examined the impact of obesity on the operative complications and recurrence in patients with endometrial cancer in an Egyptian cancer care setting. Type I endometrial cancers were more common in obese patients in our study as reported by others [12][13][14] . As regard the operative procedures, obesity did not significantly impact the surgical procedures in both groups as regard the number of patients who underwent lymphadenectomy, the median number of harvested lymph nodes and the intraoperative complications.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we examined the impact of obesity on the operative complications and recurrence in patients with endometrial cancer in an Egyptian cancer care setting. Type I endometrial cancers were more common in obese patients in our study as reported by others [12][13][14] . As regard the operative procedures, obesity did not significantly impact the surgical procedures in both groups as regard the number of patients who underwent lymphadenectomy, the median number of harvested lymph nodes and the intraoperative complications.…”
Section: Discussionsupporting
confidence: 87%
“…The first, also placed in NZ, reported similar stories of self-doubt and confusion around their symptoms. 23 The second, placed in Canada, investigated morbidly obese women diagnosed with low-grade endometrial cancer 24 and focused on barriers to surgery for this group of women. This study found that women with endometrial cancer were subject to stigma and poor provider communication, and that many of the participants learnt about the link between endometrial cancer and obesity through their own reading.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that women with endometrial cancer were subject to stigma and poor provider communication, and that many of the participants learnt about the link between endometrial cancer and obesity through their own reading. 24 Participants also noted their reluctance to seek care due to prior stigmatisation experiences. 24 These issues were similarly reported by a number of participants in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first, also placed in New Zealand, reported similar stories of self-doubt and confusion around their symptoms (19). The second, placed in Canada, investigated morbidly obese women diagnosed with low grade endometrial cancer (20) and focused on barriers to surgery for this group of women. This study found that women with endometrial cancer were subject to stigma and poor provider communication and that many of the participants learnt about the link between endometrial cancer and obesity through their own reading (20).…”
Section: Discussionmentioning
confidence: 99%